The effects of health tourism on a country’s healthcare economy: a case study of selected provinces in Iran - Kazemi Nasab Hashemabadi , Jaber; Alavi Bajgani, Seyed Ali Reza; Alavirad , Abbas (Social Determinants of Health, 2026)
Background: Iran has not enjoyed an optimal economic situation; therefore, improving the conditions for health tourism can have positive effects on the country’s economy. The primary purpose of this research was to investigate the influence exerted by medical tourism on the healthcare financial sector within the specific provinces chosen for analysis. Methods: This study was applied in nature and covers the time period from 2011–2021. The research sample included major Iranian cities (Tehran, Karaj, Qom, Isfahan, Mashhad, Shiraz, Tabriz, and Ahvaz). To evaluate how fluctuations in economic policy uncertainty influence capital expenditure within the health tourism industry, a threshold panel methodology was implemented. Results: The level of Economic Policy Uncertainty (EPU) was found to be below the threshold affecting investment in the health tourism sector. Given the positive effect above the threshold, the conclusion is that risk and uncertainty are inseparable parts of the investment process in the health tourism sector. The findings indicate that macroeconomic pressures—specifically inflation, currency volatility, and the repercussions of the COVID-19 pandemic—exerted a detrimental influence on capital allocation within the health tourism industry. Conversely, the empirical results demonstrate that financial development, market liquidity, and the volume of incoming provincial health tourists serve as significant drivers that bolster investment within this sector. Conclusion: The relationship between EPU and Investment in Health Tourism (IT) is non-linear, and the intensity and direction of this relationship depend on the level of EPU. At all levels, economic uncertainty exerts a net downward force on investment in the health tourism sector.